ANALISIS FAKTOR-FAKTOR DALAM IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 13 TAHUN 2011 TENTANG PAJAK BUMI DAN BANGUNAN PERKOTAAN (STUDI KASUS PADA KELURAHAN PETERONGAN KECAMATAN SEMARANG SELATAN KOTA SEMARANG) - Fitriariska, Rr Regina; Hidayat, Zaenal; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2014)
The transfer of Property Tax authority into Local Tax raises a variety of opportunities and challenges in its implementation. Contradictory to the achievement of the revenue target of The Property Tax, The Property Tax of Village Urban Peterongan receipts decreased in 2011 and 2012 that did not meet the target of 100% as expected. The decrease shows that the implementation of the Semarang City Regulation Number 13 Year 2011 concerning The Property Tax in the Village Urban Peterongan not run optimally. This research goals are to find the causes and solutions by decreasing in The Property Tax receipt in the Village Urban Peterongan Semarang City in line with the changes in The Local Tax Regulations regarding The Property Tax authorities into The Local Tax. To answer the purposes of analysis used descriptive qualitative research design. Â The results showed the lack of preparedness of the region, especially in the early days of the transfer of authority, particularly the Village Urban Peterongan Semarang City, in carrying out the Semarang City Regulation Number 13 Year 2011 on Property Tax. Factors inhibiting the implementation of policies derived from the intensity of the implementor disposition, law enforcement procedures, human resources, financial resources and infrastructure resources. Â Recommendations of this study are based on the dissatisfaction of the tax authorities regarding the amount of the fee collectors billing optimization property tax, village officials to submit additional personnel emoluments to DPPKAD Semarang City and then forwarded to the Mayor of Semarang City as the fulfillment of property tax service accessibility, Semarang City Government should work with banks in property tax payments